The role of solvent-solute interactions in determining crystal growth mechanisms from solution: I. The surface entropy factor - Bourne, J.R.; Davey, R.J. (Journal of crystal growth, 1976)
The surface entropy factor ( α), being dependent upon the fluid-fluid, solid-solid and fluid-solid interactions, can take on widely different values for a given solute crystallising from different solvents. Increasingly negative deviations from solution ideality depress the α-value, leading in certain cases to a rough interface with direct integration. Conversely positive deviations increase the α-value relative to an ideal solution, making a BCF mechanism on a smooth, well-defined surface more probable. These generalisations may be quantified within the framework of existing theory; their applications to a number of substances, in particular hexamethylene tetramine (HMT), are discussed. The α-value may be estimated independently of a crystallisation experiment using: (a) the heat of solution; (b) the entropy of solution, and (c) the surface and edge energies. Knowledge of the solution thermodynamics enables the most reliable estimation of α and explains why the estimate based on the heat of solution may be worthless. The α-value calculated for the growth of HMT from the vapour phase correctly predicted a BCF mechanism. The growth of this substance from aqueous and from ethanolic solutions forms the subject of Part II.